Factors associated with early tibial tuberosity fracture after tibial plateau leveling osteotomy. Issue 5 (26th July 2018) - Mehrkens, Lea R.; Hudson, Caleb C.; Cole, Grayson L.
Abstract: Objective: To determine factors contributing to tibial tuberosity fracture (TTF) after tibial plateau leveling osteotomy (TPLO). Study design: Retrospective case‐control study. Animals: Dogs (n = 2490) with cranial cruciate ligament rupture that underwent 3000 TPLO surgeries. Methods: Radiographs of 3000 stifles from dogs that underwent TPLO were reviewed for evidence of TTF. Two ratios were generated: (1) the height of the tuberosity over the width of the tibia at the most distal extent of the osteotomy (TW) and (2) the width of the narrowest point of the tuberosity over TW. Results: Twenty‐three (0.77%) cases of fracture were identified. Factors that correlated with increased odds of fracture were placement of antirotational pins distal to the insertion of the patellar ligament (PL), tuberosities with the narrowest point below the insertion of PL, placement of multiple pins distal to the PL, and bilateral simultaneous TPLO. Tuberosities that fractured were significantly taller and narrower than those that did not fracture. Rotation past the "safe point" and presence of a gap at the osteotomy were not correlated with fracture. Conclusion: Placement of multiple pins, pin placement distal to the insertion of the PL, location of the narrowest point of the tibial tuberosity distal to the insertion of the PL, and simultaneous bilateral TPLO were all associated with TTF in this study Clinical significance: Preoperative planning and postoperative assessment of TPLO should take into consideration the predisposing factors identified in this study to prevent TTF.